The Term Structure of Interest Rates in a Partially Observable Economy - Feldman, David (Journal of Finance, 1989)
This paper investigates the term structure of interest rates in a multiperiod production and exchange economy with incomplete information. Unable to observe their stochastic investment opportunities, investors engage in dynamic Bayesian inference. This results in the endogenous identification of a more complex production function which generates a richer term structure, resembling the one that actual market prices imply. In addition, this paper introduces a characteristic function of the term structure and demonstrates that, in contrast with a fully observable economy, the widely investigated expectations hypothesis holds true only if interest rates are nonstochastic.